1990
DOI: 10.1149/1.2086826
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Properties of LPCVD Titanium Nitride as a Diffusion Barrier for Silicon Device Technology

Abstract: Chemical vapor deposition has been used to deposit titanium nitride (TIN) on silicon wafers at low pressures in a coldwall single-wafer reactor. Experiments are reported for pressures in the range of 100-300 mtorr and temperatures between 450~176with titanium tetrachloride and ammonia as reactants. Both hydrogen and nitrogen are evaluated as diluents. Deposition rates as high as 1000/~/min have been achieved. The chemical nature of the films are evaluated by Auger and RBS techniques, while the morphology is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…4 -9 The high-temperature process which uses TiCl 4 /NH 3 chemistry suffers from particle contamination problems and from Cl incorporation in the film, which is of major concern for long-term device reliability. 4,5 Metalorganic CVD has been used to lower the deposition temperature which also providing conformal films. [6][7][8][9] A recent investigation involving interdiffusion in Cu/CVD TiN thin film structures found that the CVD TiN remained stable up to 450°C for 30 min, after which Cu started to diffuse into the TiN layer.…”
Section: Metalorganic Chemical Vapor Deposition Of Tantalum Nitride Bmentioning
confidence: 99%
“…4 -9 The high-temperature process which uses TiCl 4 /NH 3 chemistry suffers from particle contamination problems and from Cl incorporation in the film, which is of major concern for long-term device reliability. 4,5 Metalorganic CVD has been used to lower the deposition temperature which also providing conformal films. [6][7][8][9] A recent investigation involving interdiffusion in Cu/CVD TiN thin film structures found that the CVD TiN remained stable up to 450°C for 30 min, after which Cu started to diffuse into the TiN layer.…”
Section: Metalorganic Chemical Vapor Deposition Of Tantalum Nitride Bmentioning
confidence: 99%
“…There are, however, various limitations in employing these methods to prepare TiN thin films for microelectronic use. The processing temperature for TiN films using CVD with TiCl 4 as a source chemical requires a very high temperature, more than 600 o C [3,4]. TiN films prepared by PVD exhibit a poor stepcoverage, which makes them unsuitable for highly integrated devices [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…This frictional force can be converted into a compressive stress acting on the surface layer by dividing it by the scratch track projected area, A r The frictional force is expressed in terms of the critical load Lc, and the coefficient of friction, ~c, at this load. The final equation which relates the critical normal load with the work of adhesion, W, is given by: 1 L =~LTj (2) where A 1 is equal to:…”
Section: The Bull Et Al Model '7mentioning
confidence: 99%